2007
DOI: 10.1016/j.jpubeco.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk-return preferences in the pension domain: Are people able to choose?

Abstract: In this paper we investigate pension preferences and the effect of individual freedom of choice on risk taking in the context of pension arrangements based on a representative survey of about 1000 Dutch citizens. The attitude towards pension schemes and portfolio choices is explained by individual characteristics. Our main conclusions are the following. Risk aversion is domain dependent and highest in the pension domain. The vast majority of respondents is in favour of compulsory saving for retirement and favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 26 publications
6
98
2
1
Order By: Relevance
“…According to van Rooij et al (2012), those with higher levels of confidence in their financial knowledge are more likely to plan and save for retirement. Furthermore, Henager & Mauldin (2015) found that perceived financial knowledge is a strong indicator of saving behaviour, which supports the findings of Allgood & Walstad (2011) and Robb & Woodyard (2011). In their research, they point out that perceived financial knowledge is essential for best practices and positive financial behaviours such as paying off credit card balances, having an emergency fund, and saving for retirement.…”
Section: Actual and Perceived Financial Literacy And Financial Behavioursupporting
confidence: 59%
See 1 more Smart Citation
“…According to van Rooij et al (2012), those with higher levels of confidence in their financial knowledge are more likely to plan and save for retirement. Furthermore, Henager & Mauldin (2015) found that perceived financial knowledge is a strong indicator of saving behaviour, which supports the findings of Allgood & Walstad (2011) and Robb & Woodyard (2011). In their research, they point out that perceived financial knowledge is essential for best practices and positive financial behaviours such as paying off credit card balances, having an emergency fund, and saving for retirement.…”
Section: Actual and Perceived Financial Literacy And Financial Behavioursupporting
confidence: 59%
“…In their research, they point out that perceived financial knowledge is essential for best practices and positive financial behaviours such as paying off credit card balances, having an emergency fund, and saving for retirement. According to Clark & Strauss (2008) and van Rooij et al (2007van Rooij et al ( , 2011, individuals' attitudes and perception of financial risks are determinants of a variety of financial decisions. Benjamin et al (2013) and Dohmen et al(2010) also proved that knowledge and cognitive ability affect preferences such as risk aversion, an impact on financial decisions.…”
Section: Actual and Perceived Financial Literacy And Financial Behaviourmentioning
confidence: 99%
“…Possible limitation of examining relationship between FL and TFR is the presence of possible endogeneity. FL, as an endogenous variable, has already been recognized in the research of Van Rooij, Alessi, 2011, Van Rooij, Kool andPrast, 2007 and many others.…”
Section: Fkmentioning
confidence: 96%
“…For instance, it is seen that individuals with high levels of financial risk tolerance prefer stocks rather than bonds and certificates of deposit in their retirement funds (Hariharan et al, 2000). Van Rooij et al (2007) investigated risk attitudes towards general matters, financial matters and pension matters and found that for the decisions regarding the pension, individuals acted in the most risk-averse manner choosing the most conservative portfolios of funds. Deaves et al (2007) reported that individuals who had greater inclination to plan are more risk tolerant and make larger pension contributions.…”
Section: Financial Risk Tolerancementioning
confidence: 99%